“Avaliação do conhecimento do público leigo e profissionais de saúde sobre a cirurgia e traumatologia buco-maxilo-facial” - Pita Neto, Ivo Cavalcante (2009)
This paper describes a study assessing the knowledge of the lay public and health professionals about the oral and maxillofacial surgery in the city of Fortaleza, CE. Through questionnaires, were addressed to different groups including dentistry (group 1, n = 100) academic dentistry (group 2, n = 100), medical (group 3, n = 100), academic of medicine (group 4, n = 100), nurses (group 5, n = 100), academic of nursing (group 6, n = 100) and the lay public (group 7, n = 100) non-health professional with higher level or in course. It described several cases of clinical competence of oral and maxillofacial surgery and other not, and asked the respondents to choose a specialist to treat each case, including the plastic surgeon, the ENT, the oral and maxillofacial surgeon, the head and neck surgeon and the "other" option. The analysis consisted in the construction of contingency tables, applying the chi-square (X ²) and the extent of association of Cramer V. In comparison, bilateral tests were used where the value of the level of significance adopted in this study was α = 0.05. It was found that for fracture of nose, tongue cancer, increase in volume in the neck, cosmetic surgery of the nose and dissatisfaction with facial aesthetics, that all groups were classified as knowledge BAD. The analysis with the level of knowledge of groups, you can verify that when raised on aesthetic surgery of the nose there was no statistically significant difference with respect to knowledge of the groups. However, in assessing the level of knowledge regarding the dentoalveolar fractures, six were classified as OPTIMUM, the other (group 7, lay public) was rated as GOOD. When evaluated the removal of salivary gland, biopsy of lesions in the mouth, benign tumor of mandible, increase in volume in the mandible, children with cleft lip, palate and lip-palate, groups 3 and 4 (medical and academic medicine) were classified with knowledge BAD. To zygomatic fracture, treatment of cysts in the maxillary, mandibular graft, excessive jaw, jaw deficiency and excess of maxilla, there was also REGULAR. It was concluded that the sample of the results of the study assessing the knowledge of the data reveals CTBMF of poor knowledge in relation to groups, lack of education of society, poor perception of the population about the CTBMF with regard to area of operation, information, training and continuing education. For health professionals, especially the medical field, was found knowledge on diagnosis and surgical treatment, routing and guidance of treatment on the area of operation of the specialty (CTBMF).